1999
DOI: 10.2139/ssrn.158796
|View full text |Cite
|
Sign up to set email alerts
|

(Self-) Enforcement of Joint Implementation and Clean Development Mechanism Contracts

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…This approach might be applied to setting different rules for small and large projects (see section 3.2.2). Hagem (1996), Janssen (1999) and Fischer (2002) also consider the issues of incomplete information, adverse selection and strategic behavior in Joint Implementation. Ausubel et al (2003) develop a mechanism to reveal baselines in an auction context.…”
Section: Possible Methodologiesmentioning
confidence: 99%
“…This approach might be applied to setting different rules for small and large projects (see section 3.2.2). Hagem (1996), Janssen (1999) and Fischer (2002) also consider the issues of incomplete information, adverse selection and strategic behavior in Joint Implementation. Ausubel et al (2003) develop a mechanism to reveal baselines in an auction context.…”
Section: Possible Methodologiesmentioning
confidence: 99%
“…Janssen (1999) showed that credible enforcement on behalf of the host government on any cheating host party could guarantee implementation of a CDM contract yielding real emission reductions. The analysis holds for two private sector parties or for the case when the two actors represent national governments, and the terms host party and host country were used interchangeably.…”
Section: Technology Transfers As a Means Of Creating Countervailing Imentioning
confidence: 99%
“…Even if an early ratification of the Kyoto Protocol were obtained, some specific problems obstruct the implementation of the CDM. Incomplete information limits the efficiency gains from JI (Hagem, 1996), and Wirl, Huber, and Walker (1998) and Janssen (1999) propose some mechanisms and institutions to provide correct incentives for JI projects when there is asymmetric information between the investing party and the host party. 3 Because of the difficulties to observe the actual emission reductions, both the investing party and the host party have incentives to overstate the emission reductions created by the project: the host party in order to obtain a higher transfer payment, and the investing party in order to maximize the credits earned towards its emission reduction commitment under the Kyoto Protocol.…”
Section: Introductionmentioning
confidence: 99%
“…The host country in order to obtain a higher transfer payment, and the investing party in order to maximise the credits earned towards its emission reduction commitment under the Kyoto Protocol. Incomplete information limits the efficiency gains from JI (Hagem, 1998), and Wirl, Huber and Walker (1998) and Janssen (1999) propose some mechanisms and institutions to provide correct incentives for JI projects when there is asymmetric information between the investing party and the host party. Yet, the problem of establishing credible contracts for the CDM is somewhat different.…”
Section: Introductionmentioning
confidence: 99%